2009
DOI: 10.2307/25702539
|View full text |Cite
|
Sign up to set email alerts
|

Freight Transportation Derivatives Contracts: State of the Art and Future Developments

Abstract: In lean and demand-responsive logistics systems, orders need to be delivered rapidly, accurately, and reliably, even under demand uncertainty. Increasing burdens on the industry motivate the introduction of new methods to manage transportation service contracts. One way to hedge transportation capacity and cost volatility is to create derivative contracts. To date, ocean transportation is the only mode of transportation where this type of contract has been applied. The purpose of this article is to provide an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…No dominant, centralized marketplaces exist for buyers and suppliers to interact (Tsai et al. 2009). Hence, to establish prices and contracts, buyers typically conduct annual procurement auctions and invite suppliers to compete for future business (Caplice and Sheffi 2003).…”
Section: Background Theory and Hypothesesmentioning
confidence: 99%
“…No dominant, centralized marketplaces exist for buyers and suppliers to interact (Tsai et al. 2009). Hence, to establish prices and contracts, buyers typically conduct annual procurement auctions and invite suppliers to compete for future business (Caplice and Sheffi 2003).…”
Section: Background Theory and Hypothesesmentioning
confidence: 99%
“…We contribute by showing how a shipper can compare contract types before formulating a request for quotation. Tsai, Regan, and Saphores (2008) showed that shipper‐forwarder relationships can be coordinated using a freight transportation derivative contract, where uncertainty is hedged using real options. Brusset and Temme (2005) argued that transportation outsourcing should include a mix of long‐term contract and spot price.…”
Section: Literature Reviewmentioning
confidence: 99%